Enhanced interaction: audience engagement in entertainment events through the Bumbometer app - Martins, Gustavo; Gomes, Genildo; Conceição, Júlia Luiza; Marques, Leonardo; Da Silva, Dan; Castro, Thais; Gadelha, Bruno; de Freitas, Rosiane (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
The use of mobile devices is part of the modern scenario for interaction, work, and leisure. Their usage in entertaining events, as sports and cultural ones are easily observable. Considering those new interaction possibilities, we discuss in this work elements of crowd engagement through the use of a mobile game developed in the context of entertainment events, either with the crowd in the same place or in different locations. This game is called Bumbometer and it uses movement sensors during an interactive dynamic with the crowd using concepts from Mobile Crowd Sensing and User eXperience. Bumbometer was evaluated in two experimental studies: the first one was in a real setting of a cultural event; the second one was carried out in a controlled environment simulating a large-scale event in a social isolation scenario. Results indicate that people feel immerse and engaged during interaction through the game and they consider the game an immersive creative way for interacting in entertainment events.